Practical DV filmmaking : - Evans, Russell (Elsevier, 2004)
This book provides a practical guide to the process of making a film with low-cost digital equipment: from development through to production, post-production and distribution. The book concen trates on filmmaking principles throughout, showing how to use digital tools for innovative filmmaking